2012
DOI: 10.1039/c2ja30016h
|View full text |Cite
|
Sign up to set email alerts
|

LA-ICP-MS and nHPLC-ESI-LTQ-FT-MS/MS for the analysis of cisplatin–protein complexes separated by two dimensional gel electrophoresis in biological samples

Abstract: A method for the analysis of Pt-protein complexes in biological samples, previously subjected to cisplatin treatment, has been developed. Proteins were separated by gel electrophoresis, and those bound to Pt were detected with high sensitivity by LA-ICP-(SF)-MS. Pt-containing spots were in-gel digested with trypsin, and the peptides produced identified using nHPLC-ESI-LTQ-FT-MS/MS. The influence of protein separation conditions, staining and gel processing prior to laser ablation on Pt-protein bonds preservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
(57 reference statements)
1
36
0
Order By: Relevance
“…With the aim to provide a method that allows for detection and quantification of protein–metal adducts in gels, which are often used for the separation of a large number of proteins in complex matrices, we have used GE in combination with LA–ICP‐MS. For method development, we employed cisplatin and HSA whose reactions are well characterized . In order to be able to analyze gels by LA–ICP‐MS, a homogeneous, planar surface needs to be prepared.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the aim to provide a method that allows for detection and quantification of protein–metal adducts in gels, which are often used for the separation of a large number of proteins in complex matrices, we have used GE in combination with LA–ICP‐MS. For method development, we employed cisplatin and HSA whose reactions are well characterized . In order to be able to analyze gels by LA–ICP‐MS, a homogeneous, planar surface needs to be prepared.…”
Section: Resultsmentioning
confidence: 99%
“…This can be achieved by gel drying or through electroblotting of a nitrocellulose membrane. It has been shown that gel drying is the most efficient method and retains the quantitative features of GE . However, the gels need to be completely dry for efficient energy transfer .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ablation cell is a prototype design from D. Günther (ETH Zürich) which was already used for ablating electrophoretic gel and its design was altered by adding a second gas inlet opposite to the primary inlet [28]. Before the analysis, the system was warmed up and tuned on a daily basis by ablating glass standard (NIST 612, USA; line scans with 200 µm spot size, 10 µm s -1 scan rate, 20 Hz repetition rate and 100% laser energy).…”
Section: La-icp-ms Analysis Of 2-de Gelsmentioning
confidence: 99%
“…The corresponding 195 Pt images are shown as insets for both an unstained gel (A1, B1, C1) and a silver stained gel (A2, B2, C2). Left, inset: color scale for 195 Pt monitoring, common for all the images except for C1, which presents its own scale…”
Section: Calibrationmentioning
confidence: 99%